Self-harm in young college suicide survivors (Revista Estudios Psicológicos, 2024)
Self-injurious behaviors often arise as an attempt to regulate emotions and temporarily alleviate emotional and social pain, potentially leading to suicidal attempts over time—a complex phenomenon that demands a profound and diverse understanding of intense emotional distress and an urgent need for help and support. Thus, this article aimed to explore self-injurious experiences in survivors of suicide attempts during university years through a systematic review methodology using the PRISMA protocol, identifying and critically evaluating the quality of 24 studies spanning a period from 2003 to 2024, using keywords such as self-injury, non-suicidal self-injury, university students, adolescents, young adults, and others in databases like Web of Science, Redalyc, and Dialnet. It was found that self-injurious experiences in university students include cuts, burns, blows, pinches, falls, bites, scratches, and more, resulting from depression, anxiety, stress, impulsivity, emotional dysregulation, avoidant coping styles, psychoactive substance use, bullying, academic pressure, history of violence, existential void, fatalistic attitudes, low self-esteem, cognitive rumination, family dysfunction, negative sexual experiences, and more. The above reveals that these experiences require specialized management that includes institutional and family care and support protocols, encompassing emotional, social, and personal factors, which implies the creation of early intervention programs, continuous psychological support, and awareness campaigns to reduce the stigma associated with self-injury and suicide.
Keywords: self-destructive behavior; non-suicidal self-injury; university students; suicide attempt; completed suicide